Decision and Game Theory for Security : 6th International Conference, GameSec 2015, London, UK, November 4-5, 2015, Proceedings - Khouzani, MHR.; Panaousis, Emmanouil; Theodorakopoulos, George; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 6th International Conference on Decision and Game Theory for Security, GameSec 2015, held in London, UK, in November 2015. The 16 revised full papers presented together with 5 short papers were carefully reviewed and selected from 37 submissions. Game and decision theory has emerged as a valuable systematic framework with powerful analytical tools in dealing with the intricacies involved in making sound and sensible security decisions. For instance, game theory provides methodical approaches to account for interdependencies of security decisions, the role of hidden and asymmetric information, the perception of risks and costs in human behaviour, the incentives/limitations of the attackers, and much more. Combined with our classical approach to computer and network security, and drawing from various fields such as economic, social and behavioural sciences, game and decision theory is playing a fundamental role in the development of the pillars of the "science of security".
Keywords: Computer Communication Networks; Computer security; Computer software; Information Systems; Mathematics; Information Systems Applications (incl. Internet).; Computer Communication Networks; Systems and Data Security; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Game Theory, Economics, Social and Behav. Sciences